Identificação e caracterização da família de genes SnRKs em Psidium guajava L.: perspectivas para tolerância ao estresse salino - Fioresi, Vinicius Sartori (2021)
Salinity is one of the major problems to be faced in agriculture today, it has caused considerable losses worldwide, mainly damaging crops in arid and semi-arid regions, with a high evaporation process of surface water from the soil, a fact that further a